Amyloid PET Radiopharmaceuticals and Imaging for Clinical and Research Applications in Thailand - Siriprapa, Tossaporn; Thientunyakit, Tanyaluck; Gelovani, Juri (Siriraj Medical Journal, 2023)
In the past two decades, the research community has focused on defining reliable molecular biomarkers for the early diagnosis of Alzheimer’s disease (AD). Several PET radiopharmaceuticals have been developed and gained regulatory approval for the non-invasive detection of Aβ amyloid deposits in the brain. Nowadays, there are several PET imaging tracers available in Thailand for amyloid imaging including [11C]PiB, [18F]Florbetapir, and [18F]Florbetaben. This review provides a summary of commonly used amyloid PET radiopharmaceuticals, focusing on the available radiopharmaceuticals in Thailand and the experiences of using amyloid PET radiopharmaceuticals and imaging for clinical and research applications at Siriraj Hospital.